Reconstructing Contact Space Biographies in Sudan During the Bronze Age - Julia Budka; Hassan Aglan; Chloë Ward (Humans)
Traditional models of interaction in northern Sudan have innate Egyptological, elite, and urban biases which have relegated certain areas to mere peripheries of more ‘established’ and ‘central’ sites. In order to reach a higher resolution understanding of cultural dynamics and diversity of ancient Nilotic groups, the DiverseNile project has established the bespoke concept of Contact Space Biography which we present in the following article. We challenge existing approaches to cultural contact in the region by adopting a bottom-up approach which moves away from well-established categorisation of sites in our study area. In particular by reconstructing landscape biographies of the Bronze Age in the Middle Nile beyond established cultural categories in order to provide new insights into the ancient dynamics of social spaces, which include landscape features and non-human activities. In the following we instead consider such areas as complex social spaces intertwined with, an often changing, landscape by presenting our findings from the study of cemetery and settlement sites. Overall, the concept of Contact Space Biography effectively combines models of contact spaces, the idiosyncrasies of a changing landscape and the technological and industrial prerogatives of those living in and accessing this region.